Infection pattern and transmission potential of chikungunya virus in two New World laboratory-adapted Aedes aegypti strains - Dong, S. Z.; Kantor, A. M.; Lin, J. Y.; Passarelli, A. Lorena; Clem, Rollie J.; Franz, A. W. E. (My University, 2016)
Chikungunya virus (CHIKV) is an emerging mosquito-borne virus belonging to the Togaviridae, which is transmitted to humans by Aedes aegypti and Ae. albopictus. We describe the infection pattern of CHIKV in two New World Ae. aegypti strains, HWE and ORL. Both mosquito strains were susceptible to the virus but showed different infection patterns in midguts and salivary glands. Even though acquisition of a bloodmeal showed moderate levels of apoptosis in midgut tissue, there was no obvious additional CHIKV-induced apoptosis detectable during midgut infection. Analysis of expression of apoptosis-related genes suggested that CHIKV infection dampens rather than promotes apoptosis in the mosquito midgut. In both mosquito strains, the virus was present in saliva within two days post-oral infection. HWE and ORL mosquitoes exhibited no salivary gland infection barrier; however, only 60% (HWE) to 65% (ORL) of the females had released the virus in their saliva at one week post-oral acquisition, suggesting a salivary gland escape barrier. CHIKV induced an apoptotic response in salivary glands of HWE and ORL mosquitoes, demonstrating that the virus caused pathology in its natural vector.
Citation: Dong, S. Z., Kantor, A. M., Lin, J. Y., Passarelli, A. L., Clem, R. J., & Franz, A. W. E. (2016). Infection pattern and transmission potential of chikungunya virus in two New World laboratory-adapted Aedes aegypti strains. Scientific Reports, 6, 13. doi:10.1038/srep24729
Keywords: Equine Encephalomyelitis Virus; Valley Fever Virus; La-Crosse Virus; Sindbis Virus; Diptera-Culicidae; Vector Competence